Effects of adjuvant low-dose dexamethasone on recurrence in patients with significant residual chronic subdural hematoma after burr-hole drainage: a single-institution retrospective case-control series - Aleksandar Bojović; Milan Lepić; Stefan Mandić-Rajčević; Sanja Lepić; Svetozar Stanković; Aleksandar Djurdjević; Aleksandra Lokaj; Miloš Božić; Nemanja Rančić (Brain and Spine, 2025)
Objective: Recurrence after surgical treatment remains a significant challenge in the management of chronic subdural hematoma (CSDH). Patients with large postoperative residual collections are at increased risk, and adjuvant dexamethasone treatment appears promising as it may reduce inflammation within residual collections. Research question: This study evaluates the effectiveness of adjuvant low-dose dexamethasone treatment in reducing recurrence rates in patients with significant residual hematomas (>50 %) after burr-hole drainage. Methods: A retrospective case-control study was conducted on CSDH patients treated at the Military Medical Academy, Belgrade, from 2016 to 2023. Patients undergoing burr-hole craniostomy with postoperative residual CSDH collection >50 % of the preoperative volume were included. A subset received adjuvant low-dose dexamethasone (initial 2 mg twice daily, tapering over three weeks) decided arbitrarily by the treating neurosurgeon. Primary outcome was recurrence. Results: A total of 99 patients met the inclusion criteria, with a mean age of 74.1 years. Recurrence was observed in 16 of 70 patients (22.9 %) in the control compared to only 1 of 29 (3.4 %) in the dexamethasone group (OR = 0.12, p = 0.045). The protective effect remained pronounced in the multivariate model, and only a single mild dexamethasone adverse event was observed. Discussion and conclusion: Adjuvant low-dose dexamethasone significantly reduced recurrence rates in CSDH patients with large postoperative residual collections. These findings suggest that low-dose corticosteroid therapy may be a viable adjunct to surgical treatment, but only in cases at increased risk of recurrence. However, further prospective trials are necessary to confirm these results and establish standardized guidelines.